Elevated VEGF-plasma levels in young patients with mild essential hypertension - Stumpf, Christian; Jukic, Jelena; Yilmaz, A.; Raaz, Dorette; Schmieder, Roland; Daniel, Werner; Garlichs, Christoph (European Journal of Clinical Investigation, 2009)
Background: Growing evidence shows that inflammation plays a pivotal role in the pathophysiology of essential hypertension (EH). Vascular endothelial cell growth factor (VEGF) is currently discussed as a possible mediator of inflammation. To investigate the hypothesis that VEGF plays a role as an inflammatory mediator in EH we performed the present pilot study of young patients in a very early stage of EH. Materials and methods: 15 young patients with mild EH [33.8 ± 7.3 years, systolic blood pressure (SBP): 143.8 ± 10.5 mmHg, diastolic blood pressure (DBP): 88.2 ± 11.1 mmHg, mean arterial pressure (MAP) 106.6 ± 10.4 mmHg] and 15 healthy controls (31.7 ± 10.6 years) were examined. Blood was drawn from a peripheral vein and serum levels of VEGF, monocyte-chemoattractant-protein (MCP)-1, high-sensitivity C-reactive protein (hsCRP), interleukin (IL)-6, and tumour-necrosis-factor (TNF)-α were measured via commercially available enzyme-linked immunoassays. Results: Hypertensives showed increased plasma levels of VEGF (P < 0.05) and MCP-1 (P < 0.05). VEGF positively correlated with MAP (r = 0.46, P < 0.05) and MCP-1 (r = 0.63, P < 0.01). Multivariate analysis demonstrated VEGF to be an independent predictor of MCP-1 levels. Furthermore, hypertensives had higher levels of hsCRP (P < 0.01), IL-6 (P < 0.001) and TNF-α (P < 0.05). IL-6 levels correlated with SBP (r = 0.59, P < 0.001), DBP (r = 0.67, P < 0.001) and MAP (r = 0.46, P < 0.001). A significant positive correlation was also found between hsCRP levels and SBP (r = 0.39, P < 0.05). Conclusions: This pilot study demonstrates that in an early state of EH, inflammatory pathways have already been activated. Besides classical pro-inflammatory cytokines, VEGF serum levels are significantly elevated. The positive correlation of VEGF with MCP-1 is suggestive for the already described induction of MCP-1 via VEGF. © 2008 The Authors.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Cytokines; Hypertension; Inflammation; VEGF